Factors Affecting Revenue of Pineapple Farmers: An Empirical Study in Prachuap Khiri Khan Province - KanjanaMongkolnipath, KanjanaPrakobsaeng, NittayaManeenak, ChalongRattanapong, VijitrutBunthong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The purpose of this study was to study the relationship between individual fundamental factors of farmers namely; Cost, Liabilities, Sources of funds, income of pineapple farmers related to the nature of land ownership utilization, Distribution channels of pineapple products and external environmental factors, and income of pineapple farmers. The sample was 395 farmers. The research instruments were questionnaires. The statistics used in the research were percentage and multiple regression analysis. The results showed that the majority of farmers with 1–3 household members had experiences in planting pineapples for 1–20 years and gaining knowledge on how to grow pineapples from their parents and relatives. In addition, farmers had a monthly cost of cultivation in excess of 30,000 baht from personal investment. For the creation of liabilities, most of the respondents were related to agriculture, and had their own land with an area of less than 30 acers. Farmers sell their products to industrial plants through middlemen. and opinions that the measures to promote the consumption of fresh pineapple were the most beneficial. The income of most pineapple farmers earned more than 30,000 baht.